Structural protein markers in the avian oncoviruses. - Rettenmier, C W (1977)
The proteins of purified avian oncoviruses were analyzed by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis and isoelectric focusing. Certain members of the avian leukosis-sarcoma viruses (ALSV) had group-specific antigens with altered electrophoretic properties. (i) The p27 protein of Rous-associated virus 0 (RAV-0) had a lower electrophoretic mobility in SDS gels and a lower isoelectric point than the p27 of other ALSV. (ii) The p19 proteins of RAV-1, RAV-2, and the Bryan high-titer strain of Rous sarcoma virus had higher mobilities in SDS gels than did the corresponding protein of other viruses. This altered electrophoretic mobility was correlated with specific differences in the tryptic peptides of radioiodinated p19s. (iii) The p15 protein of RAV-7 had a lower mobility in SDS gels than did the p15 of other ALSV. These markers were used in a study of the structural proteins of subgroup E RAV-60 produced after infection of chicken embryo cells by exogenous ALSV. Although exogenous group-specific protein markers could often be identified in the subgroup E isolates, one RAV-60 had a p27 that comigrated with the p27 of RAV-0. The p19s of two other RAV-60 isolates had electrophoretic properties that were different than those of p19s from either RAV-0 or the exogenous viruses. These results support the hypothesis that RAV-60 is generated by recombination between endogenous and exogenous oncoviruses and indicate that at least the p27 encoded by RAV-0 is closely related to a protein specified by endogenous viral information in chicken cells.